DESAIN PRODUK DAN ONLINE PROMOTION DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PADA BUTIK LEGALIYA DENGAN MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING - Agustini, Martanti; Karnadi, Karnadi; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is the most important element for the continuity and perkemabangan of a company, for that Legaliya boutique must be able to choose the right marketing strategy so that it can develop and maintain the stability of the business because it is an indicator of success. The purpose of this study was to analyze and test the influence of the product and Online promotion on the Purchase decisions at the Boutique through the Customer Purchase Interest. The population in this study is the Legaliya Boutique consumer. The technique of sampling is determined by the probability- sampling. Analysis of data and testing hypotheses in this study use Structural Equation Model – Partial Least Square (PLS-SEM). The results of the hypothesis testing directly use the Smart PLS 3.0 application, show that the product design has a significant effect on consumer buying interests, Online promotion has a significant effect on consumer buying interests, Customer Interest in buying Decisions. The results of the test hypothesis are indirectly show that the Product Design variables for purchase decisions through a positive effect consumer purchase Interest, Online promotion on the Purchase Decision through Consumer Interest has a significant positive effect.